Water Valuation in the sub-bacia of Alto Piranhas in Paraíba state, Brazil - Assis, Lilian Figueirôa de; Vieira, Allan Sarmento; Olivera, Marcos Macri (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2017)
The objective was to assess the water main in the Sub-basin of Alto Piranhas, Paraíba State, using the model proposed by Leontief. The methodology outlined in the deductive method was used, is classified as descriptive and exploratory, with a quantitative approach. Were considered the main sub sectors studied, quantifying the consumption by the Total Water Footprint concept. The types of uses, from the Leontief model, as intermediate demands were used, too for the construction of input-output matrix, being the sectors to be considered to employ and combine inputs from for each sector. The analysis of the data showed that the Total Water Footprint resulted in a 254,938,290.78 consumption (m³/year). Therefore, it was possible to value water in different sectors, through the matrix-input, but it was observed that the absence of primary information associated with multiple water use was characterized as a limiting factor for the purpose of this study. Despite this limitation it was noted that the more intermediate demands placed on array of absolute values, lower the final prices to be paid by per capita water consumption, this occurred because there are contributions from one sector to the other.